Security and performance analysis of SCDSP - Mohamed Eljadi, Fardous; Alshaikhli, Imad Fakhri Taha (IIUM Press, 2016)
There are few approaches that attempt to add dynamicity to the structure of stream ciphers in order to improve their security level. SCDSP is a dynamic stream cipher that based on these approaches. It uses dynamic structure and parameters to increase the complexity of the cipher to improve its security level. The dynamic parameters are specified using bits from the secret key. In this paper, SCDSP is evaluated by conducting a performance and security analysis. Furthermore, a comparison between SCDSP and the seven winners of eSTREAM competition is performed. The results show that SCDSP is very promising for practical use.